Manajemen Kurikulum Rumah Tahfiz Syamsiyah Makam Haji Kartosuro Sukoharjo - Muhammad Nangin; Siti Masitah; Nasruddin Harahap; Aryan Torrido (LPPM Institut Pendidikan Nusantara Global, 2026)
Study aims to analyze and formulate a model for implementing religious-based curriculum management at Rumah Tahfidz, a non-formal educational institution focused on the development of the Qur'an and Islamic character. The research approach used is qualitative with library research and a conceptual approach. Data were obtained from various literature sources in the form of scientific journals, academic books, and educational policy documents relevant to curriculum management, Islamic education, and the formation of religious character. The data analysis technique was carried out through content analysis with the stages of data reduction, data presentation, and systematic conclusion drawing. The results of the study indicate that the implementation of religious-based curriculum management at Rumah Tahfidz can be developed through three main stages, namely planning, implementation, and evaluation of the curriculum integrated with Islamic values. This curriculum management model emphasizes the integration of spiritual, pedagogical, and managerial aspects so as to create a holistic educational environment. Thus, Rumah Tahfidz does not only function as an institution for memorizing the Qur'an, but also as a center for the formation of religious character that is adaptive to the challenges of the times. This research is expected to be a conceptual reference in the development of Islamic education curriculum based on religious values ​​in non-formal educational institutions